2023
DOI: 10.3390/ijms24043671
|View full text |Cite
|
Sign up to set email alerts
|

ß-Adrenoreceptors in Human Cancers

Abstract: Cancer is the leading cause of death and represents a significant economic burden worldwide. The numbers are constantly growing as a result of increasing life expectancy, toxic environmental factors, and adoption of Western lifestyle. Among lifestyle factors, stress and the related signaling pathways have recently been implicated in the development of tumors. Here we present some epidemiological and preclinical data concerning stress-related activation of the ß-adrenoreceptors (ß-ARs), which contributes to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…β3-adrenoceptor is overexpressed in tumor cells 4 . Due to Salmonella 's ability to influence the protein expression of tumor cells, we subjected the tumor cell lines to varying multiplicities of infection (M.O.I.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…β3-adrenoceptor is overexpressed in tumor cells 4 . Due to Salmonella 's ability to influence the protein expression of tumor cells, we subjected the tumor cell lines to varying multiplicities of infection (M.O.I.)…”
Section: Resultsmentioning
confidence: 99%
“…The β3-adrenoceptor is involved in obesity and metabolic disorders, but its connection to tumor therapy remains unclear. Recently, the β3-adrenoceptor was found to it overexpressed in tumor cells, and the β3-adrenoceptor plays an essential role in tumor growth, invasion, or metastasis 4 . This finding could potentially have implications for cancer research and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Confocal imaging showed that β-AR blockade reduced glioma cell migration by 20% and blood-brain barrier disruption was also significantly reduced. 35 Another study conducted a retrospective cohort study involving 218 patients to investigate the effect of BBs on recurrent GBM. They compared patients who received BBs with patients who did not receive AR-modifying drugs, and both groups were treated with bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the group of rats receiving the β‐AR antagonist survived significantly longer. Confocal imaging showed that β‐AR blockade reduced glioma cell migration by 20% and blood–brain barrier disruption was also significantly reduced 35 . Another study conducted a retrospective cohort study involving 218 patients to investigate the effect of BBs on recurrent GBM.…”
Section: Discussionmentioning
confidence: 99%